ANALISIS PENENTUAN LOKASI STRATEGIS TEMPAT PENAMPUNGAN SAMPAH SEMENTARA DI KECAMATAN KARANGANYAR TAHUN 2021 - Ahmad; Siti Fatimah; Setya Nugraha (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
The waste collection system in Karanganyar District uses TPS, one of the research sites, namely in Jungke urban village, is still getting less attention from the local government because it does not have an official TPS and there is no waste handling. The above shows that the problem of the number and capacity of TPS has not met the needs of waste services in Karanganyar District. The purposes of this research were: (1) the distribution of existing TPS locations in Karanganyar Sub-district in 2021; (2) the needs for TPS in Karanganyar Sub-District in 2021; (3) the distribution of strategic locations of TPS in Karanganyar Sub-district in 2021. This study uses a qualitative descriptive method with a spatial approach. The results of this study are: (1) Karanganyar Sub-district has 8 existing TPS; (2) Karanganyar sub-district requires 14 additional TPS; (3) The allotment of TPS in Lalung urban village is at location number 68, Bolong urban village at location number 39, Jantiharjo urban village at location number 46, Tegalgede urban village at location numbers 47 and 48, Jungke urban village at location number 19, Cangakan urban village at location number 62, Bejen urban village at location numbers 10 and 52, Popongan urban village at location number 24, Gayamdompo urban village at location number 31, Delingan urban village at location number 12, Gedong urban village at location number 11.